Seismic performance of electric transmission network under component failures. - Shinozuka, M. (Earthquake engineering & structural dynamics.)
Dealing with the transmission network of electric power systems, this paper identifies the sequential failures of receiving station components under a severe earthquake. Such failures progressively degrade the power network performance, potentially leading to a network blackout. Hence, in this paper, these components are incorporated into the network systems analysis taking their seismic vulnerability into consideration in the form of fragility curves for the evaluation of the network performance under seismic conditions. Specifically, most critical to the operation of transmission network, transformers, disconnect switches, circuit breakers and buses are integrated into the systems analysis, exploring the possibility of progressive failures of these components. The scenarios of these component failures can make it possible to estimate quantitatively direct cost of damage, emergency repair and restoration, and duration of power interruption and attendant economic losses and societal disruption.